Patterns and outcomes of vascular access in hemodialysis: a nationwide registry-based study from Romania - Gabriel Ștefan; Eugen Podgoreanu; Gabriel Mircescu (Renal Failure)
Background Vascular access type significantly influences outcomes in hemodialysis (HD) patients. Arteriovenous fistulas (AVFs) are preferred due to lower morbidity and mortality, while central venous catheters (CVCs) are associated with higher risks. This study, based on national registry data, examines vascular access patterns and their impact on mortality in Romanian HD patients.Methods A retrospective cohort analysis was conducted using Romanian Renal Registry data from patients initiating HD between 2020–2022, with follow-up until December 31, 2023. Vascular access was categorized as AVF, temporary CVC, or tunneled CVC. Survival analysis employed Kaplan–Meier curves and Cox proportional hazards models to evaluate the impact of vascular access type on mortality.Results Among 6,863 incident HD patients, 20% initiated HD with an AVF, while 55% used temporary CVCs and 25% tunneled CVCs. AVF use increased to 53% in prevalent patients. Patients starting HD with AVFs had significantly better survival (39.1 months) compared to temporary (32.5 months) and tunneled CVCs (33.9 months). Mortality risk was over twofold higher in patients with CVCs at initiation. Transitioning from a CVC to an AVF significantly improved survival (HR 0.27, 95% CI 0.23–0.31).Conclusions The high CVC use at HD initiation underscores the need for improved CKD diagnosis and pre-dialysis nephrology care in Romania. Early AVF placement or timely conversion from CVC to AVF significantly enhances survival. These findings support a patient-centered approach to vascular access, emphasizing tailored care and enhanced pre-dialysis planning to optimize outcomes.